Sted og anti-sted - om forholdet mellem person og lokalitet i Markus-evangeliet - Hallbäck, Geert (Religionsvidenskabeligt Tidsskrift, 1987)
The opposition between Galilee and Jerusalem is a well-known feature of Mark, which suggests that the localities form a specific level of meaning (theological and literary) in the gospel. Furthermore, on a text-theoretical/structuralist basis you are to expect some kind of rivalry between person representing change, and place representing stability. From this point of view the main sequences of Mark are analysed as follows: ‘The Wilderness’ forms the place of mythical re-qualification; ‘Galilee’ is the scene of a duel between the places and Jesus the anti-place, always going elsewhere; this scene is altered into ‘the way’, leading from Caesarea Philippi to ‘Jerusalem’, where the Temple is dissolved symbolically giving place to the omnipresence of the absent Christ in the Eucarist. The article concludes with some reflections on the theological perspectives of the empty tomb, representing the absence which brings meaning to presence.